2013
DOI: 10.2478/agp-2013-0012
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus minerals in tonstein; coal seam 405 at Sośnica-Makoszowy coal mine, Upper Silesia, southern Poland

Abstract: ABSTRACT:Kokowska-Pawłowska, M. and Nowak, J. 2013. Phosphorus minerals in tonstein; coal seam 405 at Sośnica-Makoszowy coal mine, Upper Silesia, southern Poland. Acta Geologica Polonica, 63 (2), 271-281. Warszawa.The paper presents results of research on tonstein, which constitutes an interburden in coal seam 405 at the Sośnica-Makoszowy coal mine, Makoszowy field (mining level 600 m), Upper Silesia, southern Poland. The mineral and chemical compositions of the tonstein differ from the typical compositions de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In comparison with the average content of oxides of major elements in the ash of coal from deposits around the world (SiO 2 = 10-45%,Al 2 O 3 = 1-11%, Fe 2 O 3 = 1.5-5.5%, , CaO = 2-45%, MgO = 1-20%, Na 2 O = 0.2-5.0%, K 2 O = 0.1-2.5%, SO 3 = 5-20% by Bouška 1980; TiO 2 = 0.88±0.03% and P 2 O 5 = 0.344±0.022% by Ketris and Yudovich 2009), the tested coal has above-average content of Al 2 O 3 (22.15%), Fe 2 O 3 (17.03%), and P 2 O 5 (0.70%; Table 2). The high content of Al 2 O 3 and P 2 O 5 in the Limnic Series of the USCB, especially in the coal from the Orzesze Beds, Załęże Beds and Ruda Beds is probably caused by tonstein partings and intrusive vulcanites in the coal seams and/or their vicinity (Kokowska-Pawłowska & Nowak, 2013;Łapot, 1992). In the USCB, as there are few signs of volcanic activity, phosphorus in coal is probably of syngenetic origin (Marcisz, 2014;Różkowska & Parzentny, 1990).…”
Section: Petrographic and Geochemical Indicators Of Coal Qualitymentioning
confidence: 99%
“…In comparison with the average content of oxides of major elements in the ash of coal from deposits around the world (SiO 2 = 10-45%,Al 2 O 3 = 1-11%, Fe 2 O 3 = 1.5-5.5%, , CaO = 2-45%, MgO = 1-20%, Na 2 O = 0.2-5.0%, K 2 O = 0.1-2.5%, SO 3 = 5-20% by Bouška 1980; TiO 2 = 0.88±0.03% and P 2 O 5 = 0.344±0.022% by Ketris and Yudovich 2009), the tested coal has above-average content of Al 2 O 3 (22.15%), Fe 2 O 3 (17.03%), and P 2 O 5 (0.70%; Table 2). The high content of Al 2 O 3 and P 2 O 5 in the Limnic Series of the USCB, especially in the coal from the Orzesze Beds, Załęże Beds and Ruda Beds is probably caused by tonstein partings and intrusive vulcanites in the coal seams and/or their vicinity (Kokowska-Pawłowska & Nowak, 2013;Łapot, 1992). In the USCB, as there are few signs of volcanic activity, phosphorus in coal is probably of syngenetic origin (Marcisz, 2014;Różkowska & Parzentny, 1990).…”
Section: Petrographic and Geochemical Indicators Of Coal Qualitymentioning
confidence: 99%
“…Previous studies have reported that alkali tonsteins developed during the early part of the Late Permian in southwestern China [51,69]. However, the geochemistry of several coal tonsteins of the Late Permian age worldwide indicates that they originated from volcanic ash fallout of silicic to intermediate composition [70][71][72][73][74][75][76]. The systematic investigation of volcanic tuff/ash is focused on the marine environment, but their origin is still uncertain [42,77,78].…”
Section: Input Of Felsic Volcanogenic Mattermentioning
confidence: 99%